The mother of all wars: long term consequences of the allied Mediterranean startegy in the Great War - Neves, Nuno Correia (2014)
This article presents an analysis of the long term implications of allied choices regarding the Mediterranean Theatre of Operations in World War One, from the political and military actions that confirmed Turkey’s entry into the war to decisions regarding the conduct of military operations and the relations between the Allied powers and local actors, in order to analyses the negative implications of failing to balance immediate military needs and long term political goals. In order to do so the article presents a brief analytical summary, organized geographically, of the main operations and their long term effects in each region, leading to a global overview of the allied strategy and its role in establishing the bases of the historic narratives and political realities of Mediterranean actors, such as the nature of the Turkish state, the evolution of Middle Eastern nationalisms and Islamic fundamentalism.